From Fitness To Wellness; How Something Unexpected Transformed All - Terán Velazco, César (2024)
Holos, a Peruvian online platform that connects users with wellness partners, faced a crisis during the COVID-19 pandemic. With the fitness industry severely affected, the company had to reinvent its business model, expanding from fitness to holistic wellness and adopting a new approach. However, significant challenges arose related to cost structure and pricing strategy.